Code and messages interpretation on COVID-19 street banner: Social semiotics - Lestari, Febrika Dwi; Simarmata, Rina Octavia; Sitorus, Nurhayati; Sidabutar, Usman (Linguistics and Culture Review, 2021)
COVID-19 Street banner is one of various ways and medias used for communicating and informing about the virus that contain of whether invitation, prohibition, or strategies to reduce the spread of Corona virus outbreak to society. Based on an interdisciplinary theoretical framework, this study revealed to the genaral understanding of the COVID-19 banners and how this media contribute to the overcoming of the pandemic spreading. In order to examine and explain the interpretations and influences of this media associated with the awareness and information on how to reduce the COVID-19 outbreak through the images and verbal signs of the banner, this present work analyzed COVID-19 street banner that circulated on the street and building around Medan to Binjai about COVID-19. The study employed the theories of social semiotics by using Barthes theory with descriptive visual study design approach to reveal the code and message of the banner. The result showed that those banners conveyed the similar message that doing the heath protocols are able to reduce the spreading of the virus and they have special effect on society. Government ministry and various organizations worked together to educate and encourage society about COVID-19 through street banners as their communicative strategy.